Prognosis, immunological features and potential mechanisms of HKR1 in prostate cancer via single-cell and bulk RNA-sequencing - Jing Zhai; Shiwei Liu; Tiantian Wang; Yi Wang; Yu Peng (BMC Cancer)
Abstract Background Given the limitations of conventional therapies in prostate cancer (PCa) management, identifying novel biomarkers capable of predicting tumor prognosis and immunotherapy response is critically important. This article revealed the prognosis, immunological characteristics, and potential mechanisms of HKR1 in PCa via bulk and single-cell RNA sequencing (scRNA-Seq). Methods Bulk and scRNA-Seq analyses of HKR1 in PCa were collected from online databases. Differential expression and Cox regression analyses were carried out to evaluate its expression and prognosis values in PCa, respectively. Correlation analyses were performed to evaluate associations between HKR1 expression and enriched pathways, immune cell infiltration, and other relevant biological processes. Results HKR1 showed higher expression in PCa than in normal tissues, as verified by qPCR in both PCa cell lines and tissue samples (p < 0.05). ScRNA-seq analysis demonstrated HKR1 expression in malignant cells, epithelial cells, and immune cell populations. Moreover, PCa sufferers with higher HKR1 expressions were linked with poorer prognoses, and Cox regression analysis suggested it was an independent indicator in PCa (p < 0.05). Further, we shed light on the fact that the toll-like receptor, the TGF-beta, and the p53 pathways were significantly related to HKR1 expression in PCa. HKR1 was also found to be markedly linked to immunity in PCa (p < 0.05). Notably, we characterized two novel lncRNA-RBP-HKR1 regulatory axes that potentially modulate HKR1 transcriptional dynamics in prostate carcinogenesis. Conclusions HKR1 played an undeniable role in the prognosis and immunological potential of PCa, providing evidence for the molecular mechanisms of HKR1 in PCa.